Development of flexible polymer sheet with high surface durability using discretely embedded micro-balls. Issue 1 (2017) - Wang, Do-Young; Kim, Chang-Lae; Kim, Dae-Eun
Abstract: A flexible PDMS sheet with high surface durability was developed using a novel coating concept. Instead of using a continuous hard coating to protect the polymeric sheet, the strategy was to use a discrete coating structure comprised of borosilicate glass micro-balls that were partly embedded into the surface. The hard micro-balls served to lower the contact area against the counter surface, thereby significantly lowering the friction and wear. Furthermore, by using the discrete coating structure the inherent flexibility as well as transparency of the PDMS sheet could be maintained. FEM analysis was used to understand the contact behavior of micro-balls.